Media Game Resident Evil 8 - Village dalam Pembelajaran Keterampilan Membaca dan Menulis - Mohammad Zainal Hamdy; Wiwik Prasetyo Ningsih (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2022)
The teacher is the most influential person in the formation and personal direction or character of students. Therefore, as Arabic language teachers are required to always be creative and innovate in terms of the learning process so as not to reduce students' interest in learning Arabic and not turn to foreign languages ​​that are considered fresher and newer such as Mandarin, German, or French. A good learning process requires materials, methods, media, and teacher creativity to attract students' interest in learning Arabic. The use of learning media is one aspect that can affect interest in learning Arabic. Without the media, interest in learning languages ​​can be reduced, especially for beginners. Resident Evil 8 Game – Village is one of the games in which it contains secret messages that must be understood and solved from various missions that must be completed. This study will explain how the process of learning Arabic using the media Game Resident Evil 8 – Village in PP. Darul Lughah wal Qur'an so that it will become a benchmark for other Arabic teachers when teaching Arabic, one of which is by using media that is preferred by students who mostly like games rather than studying. By using this media, students will not feel that they are learning.